4.3 HIPPOCAMPAL SUBFIELDS AND VISUOSPATIAL ASSOCIATIVE MEMORY ACROSS STAGES OF SCHIZOPHRENIA-SPECTRUM DISORDER. (9th April 2019) - Wannan, Cassandra; Cropley, Vanessa; Chakravarty, Mallar; Rheenen, Tamsyn Van; Mancuso, Sam; Bousman, Chad; Everall, Ian; McGorry, Patrick; Pantelis, Christos; Bartholomeusz, Cali
Abstract: Background: Previous studies indicate that visuospatial associative memory ability deteriorates over the course of psychotic illness, with substantial impairments observed in individuals with chronic schizophrenia. However, the neural underpinnings of poor performance on this task in schizophrenia have not previously been investigated. While previous studies have identified relationships between hippocampal volumes and memory performance in schizophrenia, few studies have examined the role of hippocampal subfields in illness-related memory deficits, and no study has examined potential differences across varying illness stages. The current study aimed to investigate whether individuals with early and established psychosis exhibited differential relationships between visuospatial associative memory and hippocampal subfield volumes. Methods: Measurements of visuospatial associative memory performance and MRI scans were obtained from 52 individuals with a chronic schizophrenia-spectrum disorder, 28 individuals with first-episode psychosis (FEP), 52 older healthy controls, and 28 younger healthy controls. Results: Both chronic and FEP patients had impaired visuospatial associative memory performance relative to healthy controls. However, only chronic patients showed hippocampal subfield volume loss relative to healthy controls. Both chronic and FEP patients demonstrated relationships between visuospatial associative memory performance and hippocampal subfield volumes in the CA4/dentate gyrus and the stratum that were not observed in healthy controls. There were no group by volume interactions when chronic and FEP patients were compared. Conclusions: The current study extends the findings of previous studies by identifying particular hippocampal subfields, including the hippocampal stratum layers and the dentate gyrus, that appear to be related to visuospatial associative memory ability in individuals with both chronic and first-episode psychosis. These regions are particularly vulnerable to the effects of chronic stress and inflammation, suggesting that these factors may contribute to memory impairment in psychotic disorders.